Higher Dietary Choline Intake Is Associated with Lower Risk of Nonalcoholic Fatty Liver in Normal-Weight Chinese Women. Issue 12 (15th October 2014) - Yu, Danxia; Shu, Xiao-Ou; Xiang, Yong-Bing; Li, Honglan; Yang, Gong; Gao, Yu-Tang; Zheng, Wei; Zhang, Xianglan
Abstract: Background: Choline deficiency has been shown to induce liver fat accumulation in both rodent and human studies. However, it is unclear whether dietary choline intake is related to fatty liver in the general population. Objective: We examined the association between choline intake and nonalcoholic fatty liver. Methods: Participants included 56, 195 Chinese women and men, 40–75 y of age, with no or negligible alcohol consumption and with no history of hepatitis, cardiovascular disease, or cancer. All participants reported undergoing liver ultrasonography. Fatty liver was defined by self-report of a physician diagnosis. Habitual dietary intakes were assessed via validated food-frequency questionnaires. Results: The average total choline intakes were 289 ± 85 mg/d in women and 318 ± 92 mg/d in men. Major food sources were eggs, soy foods, red meat, fish, and vegetables. A higher choline intake was associated with lower risk of fatty liver; after adjustment for sociodemographic characteristics, lifestyle factors, and other dietary intakes, the ORs (95% CIs) for the highest vs. the lowest quintiles of choline intake were 0.68 (0.59, 0.79) in women and 0.75 (0.60, 0.93) in men (both P -trend < 0.01). The inverse association was attenuated after further adjustment for history of metabolic disease and, in particular, BMI. The corresponding ORs (95% CIs) were 0.88 (0.75, 1.03) in women ( P -trend = 0.05) and 0.85 (0.68, 1.06) in men ( P -trend = 0.09). Stratified analyses suggested a potential effect modification by obesity status in women; the OR (95% CI) across extreme quintiles was 0.72 (0.57, 0.91) in normal-weight women vs. 1.05 (0.84, 1.31) in overweight or obese women ( P -trend = 0.007 vs. 0.99, P -interaction < 0.0001). Conclusion: Higher dietary choline intake may be associated with lower risk of nonalcoholic fatty liver only in normal-weight Chinese women.